The Holistic Nursing Competencies and Instruments for Critically III-Patients: A Scoping Review - Ismail, Suhartini; Sohilait, Hana Priscilla Frudence; Erawati, Meira (Poltekkes Kemenkes Palu, 2024)
The holistic nursing approach is an extensive model covering all aspects of care, including the patient's psychological, spiritual and social needs. Critically ill patients areas requires a holistic approach because the problems that arise are not just physical problems, but also emotional, mental and cultural in nature. The aim of this study was to determine holistic nursing competencies for critically ill patients and the instruments of holistic competencies from several literatures. The review used Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines as the analysis method. There were 17 articles reviewed from data found in several reputable databases. Searching for related literature, this article uses data based on Science Direct,Scopus, Pro-Quest,Research Gate and SpringerLink.Liiterature search using Booleon operators